2013
DOI: 10.1073/pnas.1222577110
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of somatic single-nucleotide and copy-number mutations in uterine serous carcinoma

Abstract: Uterine serous carcinoma (USC) is a biologically aggressive subtype of endometrial cancer. We analyzed the mutational landscape of USC by whole-exome sequencing of 57 cancers, most of which were matched to normal DNA from the same patients. The distribution of the number of protein-altering somatic mutations revealed that 52 USC tumors had fewer than 100 (median 36), whereas 5 had more than 3,000 somatic mutations. The mutations in these latter tumors showed hallmarks of defects in DNA mismatch repair. Among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
274
4
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 291 publications
(309 citation statements)
references
References 38 publications
22
274
4
2
Order By: Relevance
“…Mutation spectrum analysis revealed a paucity of transversion mutations in the high-mutation group, a signature often observed in mismatch repair-deficient tumors. Mutation rates, mutation spectra, and the fraction of genome affected by CNV among the remaining 37 tumors were similar to those numbers previously reported for uterine and ovarian carcinomas (8)(9)(10).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Mutation spectrum analysis revealed a paucity of transversion mutations in the high-mutation group, a signature often observed in mismatch repair-deficient tumors. Mutation rates, mutation spectra, and the fraction of genome affected by CNV among the remaining 37 tumors were similar to those numbers previously reported for uterine and ovarian carcinomas (8)(9)(10).…”
Section: Resultssupporting
confidence: 87%
“…The results identified eight genes with recurrent somatic missense mutations (Table 1). These mutations included known activating mutations in the oncogenes PIK3CA (PI3-kinase subunit alpha) and KRAS (Kirsten rat sarcoma viral oncogene homolog), a recurrent mutation in PPP2R1A (phosphatase 2a regulatory subunit) that causes loss of normal regulation of serine-threonine phosphatase 2a (11), a known recurrent mutation (N1459S) in BCOR (BCL6 corepressor) that is likely gain of function (8), and a known recurrent mutation in CHD4 (DNA helicase) (9). There were also known recurrent mutations in the tumor suppressors TP53 (tumor protein P53) and PTEN (phosphatase and tensin homolog).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, in a separate study, POLE EDMs were detected in 9% of uterine serous carcinomas and were all associated with an ultramutator phenotype. 8 Unlike previous reports, in the study by Billingsworth et al, POLE mutations were identified both in cancers with MSS and in those with MSI; of the 306 tumors with MSS, 18 (5.9%) harbored POLE mutations, and 12 of the 229 tumors with MSI had POLE mutations (5.2%). Although POLE mutations were significantly more common in MSI tumors that lacked MLH1 methylation, the authors reported 4 tumors with both POLE mutations and MLH1 silencing; this was an unexpected finding, because previous reports have suggested that MLH1 silencing and POLE EDMs are mutually exclusive.…”
contrasting
confidence: 65%